Synchronization Of Estrus With Double Dose Of Pgf2α In Cows - Deshmukh, S.G.; Pawshe, C.H.; Sahatpure, S.K.; Bankar, P.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Synchronization of estrus is one of the alternatives for the control and manipulation of reproduction. Synchronization of estrus with prostaglandin (PGF2α) and its potent analogue has been reported to be much beneficial in cattle breeding program. PGF2α had been shown to improve conception rate in cross bred cows (Senthil Kumar et al., 2007, Pattnaik et al., 2010). Utage et al. (2011) reported that Crestar ear plant + PGF2α induced estrus in buffalows by 83.33 per cent. The mode of action of PGF2α in animal with respect to control and manipulation of reproductive cycle, involves regression of corpus luteum.